Cabur Bulung dalam Perkawinan Adat Karo: Studi di Kecamatan Dolat Rayat, Kabupaten Karo - Marini, Marini (Rechtsnormen Jurnal Komunikasi dan Informasi Hukum, 2023)
Karo Cabur Bulung marriage aims to cure disease and avoid bad things from happening based on a hunch. Apart from being a belief in curing disease, the Cabur Bulung marriage is also carried out at the same time to bring a mother's family relationship closer to her Turang, or Anak Beru to Kalimbubu. The problem in this research is the procedure for implementing the Cabur Bulung marriage which is carried out on the Karo indigenous people in Kubucolia Village, Dolat Rayat District. The legal consequence is that the Cabur Bulung marriage which is carried out is not followed up by marriage until adulthood according to Karo customary law. legal protection for children who carry out Cabur Bulung marriages based on Karo customary law and positive law in force in Indonesia. The type of research used in writing this thesis is empirical juridical. The nature of this thesis research is analytical descriptive. The data used as material to analyze this thesis research are primary data and secondary data. The data collection tool in this research will be carried out by means of field studies. The analysis used by means of qualitative analysis.